2022
DOI: 10.1002/jmv.27811
|View full text |Cite
|
Sign up to set email alerts
|

A fourth dose of Omicron RBD vaccine enhances broad neutralization against SARS‐CoV‐2 variants including BA.1 and BA.2 in vaccinated mice

Abstract: The SARS‐CoV‐2 vaccines have been widely used to build an immunologic barrier in the population against the COVID‐19 pandemic. However, a newly emerging Omicron variant, including BA.1, BA.1.1, BA.2, and BA.3 sublineages, largely escaped the neutralization of existing neutralizing antibodies (nAbs), even those elicited by three doses of vaccines. Here, we used the Omicron BA.1 RBD as a fourth dose of vaccine to induce potent Omicron‐specific nAbs and evaluated the broadly neutralizing activities against SARS‐C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…1a ). In this study, we constructed two pseudotyped BA.4/5 and BA.2.75 viruses based on our previous established methods for Pango lineage A (wild-type, WT) and BA.2 17 19 . Then, we measured the neutralizing antibody titers in plasma samples obtained from 34 individuals with BA.2 breakthrough infections (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a ). In this study, we constructed two pseudotyped BA.4/5 and BA.2.75 viruses based on our previous established methods for Pango lineage A (wild-type, WT) and BA.2 17 19 . Then, we measured the neutralizing antibody titers in plasma samples obtained from 34 individuals with BA.2 breakthrough infections (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study showed that the second mRNA booster dose induces broadly neutralising antibodies (bNAbs) that are effective against BA.1, BA.1.1, BA.2 and BA.3 Omicron subvariants. 56 A UK clinical trial, COV-BOOST, demonstrated similar findings; the second mRNA booster significantly increases both cellular and humoral immunity to a level that is equal to or exceeds the first mRNA booster and is well-tolerated. 57 However, there was also evidence of limited additional boost from the second booster when pre-booster immunity is already high.…”
Section: Evidence For the Second Boostermentioning
confidence: 79%
“…The hybrid-immunity group consisted of recovered patients who received different numbers of vaccine doses, including 105 individuals with one dose, 160 individuals with two doses, and 136 individuals with three doses. A total of 833 doses of inactivated COVID-19 vaccines, including WIBP-CorV (360, 43.22%), BBIBP-CorV (142, 17.05%), CoronaVac (307, 36.85%), and KCONVAC 26 (24, 2.88%), were used to vaccinate 401 recovered patients. These four inactivated vaccines were all developed based on the SARS-CoV-2 prototype strain, sharing similar production techniques in which all the SARS-CoV-2 vaccine strains were cultured in Vero cells, inactivated by β-propiolactone, and mixed with an aluminum hydroxide adjuvant 16 , 27 29 .…”
Section: Resultsmentioning
confidence: 99%